Determinants of GHG emissions for a municipal economy: Structural decomposition analysis of Chongqing. (15th June 2017) - Hu, Yi; Yin, Zhifeng; Ma, Jian; Du, Wencui; Liu, Danhe; Sun, Luxi
Highlights: SDA includes the effects of both production and final demand. Explore the determinants of municipality-level emissions. Final demand drove GHG emissions growth. The change of intensity effect and production structure reduced GHG emissions. Abstract: The prefecture-level municipality of Chongqing, in western China, is the largest and most populous city in China. Chongqing's uniqueness presents multiple challenges, including that greenhouse gas (GHG) emissions abetment requirement of the city is greater than that of other Chinese cities. This paper explores factors behind change in aggregate greenhouse gas (GHG) emissions in Chongqing, including differences at the sector level. We use a structure decomposition analysis (SDA) method to quantify sources of emissions growth. Results indicate that the crucial factors that drive GHG emissions reduction relate to intensities and input-output structure; and that the main driver of emissions growth was increasing final demand. The analysis also reveals that the mining and coal-washing sector and the metals melting and rolling sector were the main sources of GHG emissions in Chongqing.